Protective effect of Gelofusine against cRGD-siRNA-induced nephrotoxicity in mice - Liao, Wenjie (Ren Fail, 2018)
Based on successful targeting to the αvβ3 integrin of cyclic arginine–glycine–aspartic acid (cRGD), cRGD-conjugated small interfering RNA (siRNA) exhibits tumor targeting and has become a new treatment strategy for solid tumors. However, the nephrotoxicity caused by its renal retention limits its clinical application. Here, we evaluated the protective effect of Gelofusine against cRGD-conjugated siRNA-induced nephrotoxicity in mice. Male Kunming mice (six per group) were either co-injected with Gelofusine and cRGD-siRNA or injected with cRGD-siRNA alone. After administration of these treatments five times, creatinine and blood urea nitrogen (BUN) levels were determined. Hematoxylin–eosin staining (HE staining) and transferase dUTP nick end labeling (TUNEL) analysis were used to compare the difference in renal damage between the groups. Additionally, fluorescence imaging was used to observe the distribution of cRGD-siRNA in vivo. The group co-injected with Gelofusine and cRGD-siRNA displayed lower creatinine and BUN levels than the cRGD-siRNA-alone group and showed less renal damage upon HE staining and TUNEL analysis. Gelofusine decreased the retention time and accelerated the elimination of cRGD-siRNA from the organs, as observed in the fluorescence images. These data indicate that Gelofusine significantly increased the excretion of cRGD-conjugated siRNA and reduced the associated renal damage.